AMERICAN AND INDONESIAN SITCOMS: A TRANSNATIONAL ANALYSIS ON “FRIENDS” AND INDONESIAN SITCOMS - Teguh Puja Pramadya (Universitas Gadjah Mada, 2016)
The fact that Indonesia adopts many programs from American popular culture, especially the situation comedy format, makes reruns and reduplications at the national level, and makes them into primetime programs on most of the private television at stations demonstrates the strength of American cultural influence in Indonesia. Although, there are differences and adjustments in some parts of the program, modifying to the culture and customs of the people of Indonesia. The question arises, whether the entertainment producers in Indonesia nowadays were deliberately imitating and duplicating some imported variety and comedy format for the sake of popularity in public television in Indonesia or whether the traditional format of comedy in Indonesia is now being replaced with variety and comedy formats imported from America.This study is carried out in the framework of American Studies. To carry out the analysis, the writer made use of the grounded research and comparative study approach and Stuart Hall's theory of representation, to see the scope for negotiation and opposition on the part of the audience as an active part of the media consumption and how audience members make meanings and understand reality through their use of cultural symbols in both print and visual media. The object of the study is limited to the representation in Friends, as an example of an American sitcom, and to the representation in four Indonesian sitcoms, namely Keluarga Masa Kini, Tetangga Masa Gitu, Saya Terima Nikahnya and The East.The findings of selected episodes in Friends and Indonesian sitcoms, indicate some similarities and differences towards the trends that sitcoms have used. It is likely that American and Indonesian sitcoms use almost the same conventions of sitcom narrative, but, they also show some differences towards the content of the show, several changes and transformations in the narrative structures can be seen, especially in terms of the locality of each sitcom in depicting the values from the social and cultural construction where the sitcom is made. Another important thing to be taken into account is the way each society has a different construction of gender roles and sexuality, family values and so on, that lead to a different cultural product although they use and share the same conventions and characteristics of the sitcom.Keywords: sitcom, representation, social construction, gender, family